การกำจัดอิออนโลหะหนักในน้ำเสียโดยไคโตแซน - เกษม สีดอกบวบ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research was aimed to study the removal efficiency of chitosan on 5 heavy metal ions; i.e., Cu2+, Zn2+, Cd2+, Pb2+, and Hg2+, from industrial and laboratory wastewater. The study was separated into 3 parts; i.e., preparation of chitosan from shrimp and crab shells, determination of optimum pH and optimum dose and removal efficiency analysis. The wastewater was taken from 5 sources; i.e., industrial wastewater from General Environmental Conservation Public Company (Genco), Siam Battery Industry Co., Ltd., Thai Asahi Chemical Co., Ltd., and laboratory wastewater from Chemical Laboratory Building 1 and 2 of Department of Chemistry, Faculty of Science, C.U. The chitosan yields, average molecular weight, and degree of deacetylation were 25.9% and 29.9%, 3.3x10x10x10x10x10 and 2.7x10x10x10x10x10 Dalton, 93-94% and 98% of dried shrimp and crab shells, respectively. For Genco wastewater, it consisted of 3 interest ions; i.e., Cu2+, Zn2+, and Cd2+. The optimum pH was 5.5. The optimum doses and removal efficiencies with 24 hr settling times were 1.5 g/400 ml and more than 76.9, 66.4-95.5, 73.1-79.8, respectively. For Siam Battery Industry Co. wastewater, it consisted of 1 interest ion; i.e., Pb2+. The optimum pH was 5.5. The optimum doses and removal efficiencies with 24 hr settling times were 1.7 g/400 ml and more than 90.3 For Thai Asahi Chemical Co. wastewater, it consisted of 1 interest ion; i.e., Hg2+. The optimum pH was 5.0. The optimum doses and removal efficiencies with 24 hr settling times were 2.2 g/400 ml and more than 97.8. For Chem. Lab. Build. 1 wastewater, it consisted of 4 interest ions; i.e., Zn2+, Cd2+, Pb2+, and Hg2+. The optimum pH was 5.5. The optimum doses and removal efficiencies with 24 hr settling times were 1.5 g/400 ml and 94.5-97.7, more than 14.9 66.4-67.6, 48.0-76.7, respectively. For Chem. Lab. Build. 2 wastewater, it consisted of 1 interest ion; i.e., Cu2+. The optimum pH was 5.5. The optimum doses and removal eficiencies with 72 hr settling times were 8.0 g/400 ml and more than 96.4